Search for resonant pair production of neutral long-lived particles decaying to bb̄ in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We report on a first search for resonant pair production of neutral long-lived particles (NLLP) which each decay to a bb̄ pair, using 3.6fb-1 of data recorded with the D0 detector at the Fermilab Tevatron collider. We search for pairs of displaced vertices in the tracking detector at radii in the range 1.6-20cm from the beam axis. No significant excess is observed above background, and upper limits are set on the production rate in a hidden-valley benchmark model for a range of Higgs boson masses and NLLP masses and lifetimes. © 2009 The American Physical Society.
Keywords: Beam axis; Benchmark models; Fermilab Tevatron collider; Higgs boson; Pair production; Production rates; Tracking detectors; Upper limits; Photons; Tellurium compounds; Bosons